Cooking fuel as a risk factor for adenoid hypertrophy in children aged less than five living in an informal settlement, Nairobi County, Kenya - Senewa, Anne; Pertet, Anne M.; Otieno-Odawa, Careena (International Journal of Contemporary Pediatrics, 2018)
Background: Fuels used for cooking are major sources of household air pollution, which lead to increased prevalence of upper respiratory tract infections and allergic conditions especially in children. The aim of present study was to investigate whether fuels used for cooking were risk factors for adenoid hypertrophy in children. Methods: Authors used a case-control study design where the exposure was cooking fuel and the disease was adenoid hypertrophy. Cases were children where a post nasal space x-ray showed enlargement of the adenoids. The controls were children with no adenoid hypertrophy or related diseases. The sample consisting of 112 children was hospital based. Parent-administrated questionnaires were used to collect information on cooking fuel. Results: Cooking gas and charcoal were associated adenoid hypertrophy. Adjusted odds ratio (OR) were 1.092 for charcoal and 3.516 for gas. Children in households where gas was predominantly used for cooking were three times more likely to have enlarged adenoids. Conclusions: Exposure to cooking gas which emits nitrogen dioxide was a primarily risk for adenoid hypertrophy. Larger community-based studies are recommended to come up with evidence that guides policy concerning use of household fuels and adenoid hypertrophy.